Dynamics of heat and mass transfer: Ree-Eyring nanofluid flow over a Riga plate with bioconvention and thermal radiation - Loganathan, K.; Alessa, Nazek; Jain, Reema; Ali, Farhan; Zaib, Aurang (Frontiers in Physics, 2022)
Following improvements in devices used in biomedical engineering, cancer treatments, and thermal extrusion systems, this report explores the dynamics of Ree-Eyring nanofluid when subject to free convection, bioconvection, heat source, and thermal radiation over a convection-heated Riga plate. Bioconvection is assessed in light of the movement of the motile microorganisms that stabilize the dispersion of nanoparticles in the fluid. The impact of thermophoresis and Brownian motion, critical in the flow of heat and mass is also considered, together with the convective boundary condition. In many manufacturing sectors, non-Newtonian nanofluid flow is a crucial cooling component. Based on these factors, partial differential equations—the governing equations that model the transportation phenomena—are converted into nonlinear ordinary differential equations using the relevant relations. Finally, the nonlinear differential equations are solved using the homotopy analysis method (HAM), and the solutions are displayed in graphs representing distinct fluid flow parameters. It is conclusively found that the skin friction coefficient increases as the mixed convection parameter value rises, while the opposite effect is seen as the bioconvection Rayleigh number grows.